The Current Market of Pharmacological Drugs for the Prevention and Treatment of Obesity in Ukraine: A Review - Smetanina, Kateryna (My University, 2023)
Obesity is one of the problems of current century, which is the cause of complex disorders of organs and systems of the human body, up to the development of lethal outcomes. The modern market of pharmaceutical medicine preparations for treatment and prevention is quite extensive. The main treatment of diseases that is proven on the basis of evidence, including for preventive purposes, is the inclusion of such drugs in fever protocols throughout the country. The purpose of this study is to examine the current market of drugs for the prevention and treatment of obesity in Ukraine.
Keywords: Obesity; Medicinal Plants; Medicines; Drug registration